(3TQM GdafGQj Ydi EjSGZhLj GdahGFO GdafGQjIs - (3GdafGQj (B( (3GdaQfj (B)(3, GdQhej, TeS GdOjf, eMeO Hf MeRI Hf eMeO, J (B834 (3g`s
(3ChdgG (B:s
(3MeOG dc Gddge Ydi eG dNUJ dj ef efM YhGQa GdCaGVd Cf CcJH ahGFO dGFbI HeWGdgYI GdENhGf daQGFO GdQSGdI GdCHgQjI aj GdejRGf TQYJ ajg YOhI jhe ef CbUQ GdCjGe hNJeJ eY CPGf eZQHg HYhf Gdedc GdYdGe s
(3GdJCQjN ef QSGdI EjSGZhLj GdeDQNI aj GdeLehY HNW bQjH Ch eWGHbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6/110s
(3cTa GdXfhf (B1/207s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdadSaI hGdefWbs